Dementia 13 - Coppola, Francis Ford, 1939-; Corman, Roger, 1926-; Campbell, William, 1923-2011; Anders, Luana, 1938-1996; Patton, Bart; Filmgroup Productions; Cinetel Films ([Los Angeles, CA] : [Filmgroup Productions], 1963)
When her husband John has a heart attack while out in a rowboat on the lake, Louise Haloran throws his body overboard and later tells the family that he has left on an urgent business trip. Her main concern is that she can only inherit a part of the family fortune if if her husband is alive. The Halorans are a strange family, still grieving over the death of the youngest daughter Kathleen who drowned in a pond when she was just a child. They hold an annual ceremony of remembrance every year on the anniversary of her death. This year however, someone is wielding an ax intent on murder. --
Originally released as motion picture in 1963 and distributed by American International Pictures.
Movie distributed by Cinetel for Digitalia Film Library.
William Campbell; Luana Anders; Bart Patton; Mary Mitchel, Patrick Magee, Ethne Dunn
Cinematographer, Charles Hanawalt; editors, Mort Tubor and Stuart O'Brien ; second unit written and directed by Jack Hill; music, Ronald Stein.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 31, 2015)
Keywords: Murder -- Drama; Nobility -- Ireland -- Drama; Horror films; Fiction films; Internet videos; Streaming video